Analysis of Ring Yarn Properties Produced from Different Traveller Brands - Siddiqua, Toufiqua; Iqbal, S. M. Farhana (European Scientific Journal, ESJ, 2019)
A traveller is the tiny but significant part in ring frame in a short staple spinning mill. It is a small portion among all the parts of ring machine. It performs two most significant tasks like twisting without which spun yarn production cannot be imagined, and it aids in the winding of yarn on the cop. The traveller is one of the mechanical reasons for the hairiness properties of yarn. Two yarn of 30’s Ne KH (Card hosiery) was produced by using two same number of the traveller of different brands called Lakshmi Ring Travellers (LRT) and X-AXIS. All the processing parameters remained the same during the production of yarn. After that, Uster Evenness Tester 5 machine was used to determine the yarn properties such as unevenness percentage, imperfection index, hairiness, standard deviation of hairiness, standard deviation of hairiness in reference length 1 meter, and standard deviation of hairiness in reference length 3 meters. The end breakage rate was recorded through whole doff for the duration of the production of yarn in ring section. Statistical analysis used t-test to pair two samples to obtain the means for unevenness percentage, imperfection index, and hairiness. This was accomplished with Microsoft Excel 2013. Lakshmi Ring Travellers indicate better results than X-AXIS traveller. It can be decided from the t- test that there is no significant difference in unevenness and hairiness except imperfection index of two brands.